Analysis of the impact of radiotherapy on long-term treatment results in patients with malignant salivary gland tumors - V. T. Vayradyan; A. M. Mudunov; R. I. Azizyan; I. A. Zaderenko; S. B. Alieva; N. V. Rurua; T. T. Kondrat’eva; V. D. Ermilova (Опухоли головы и шеи, 2016)
Objective: to investigate the efficiency of radiotherapy for malignant salivary gland tumors and to reveal prognostic factors influencing overall and relapse-free survival rates in this patient group.Materials and methods. The retrospective and prospective data of 111 patients with malignant salivary gland tumors were analyzed. All the examinees received preoperative radiotherapy to the primary focus and, if need be, regional metastatic areas; the cumulative focal dose was 40–65 (56.0 ± 8.9) Gy. In the following step, the patients were surgically treated. They were divided into 2 groups according to the degree of therapeutic pathomorphism: 1) Degree 0–III (91.9 %) and 2) Degree IV (8.1 %).Results. Five- and ten-year overall survival rates were 60.1 ± 5.1 and 50.4 ± 5.7 % and 7.5 ± 11,69 and 87.5 ± 11.69 % (unachieved median) in Groups 1 and 2, respectively (p = 0.04); relapse-free survival rates were 53.6 ± 5.1 and 41.33 ± 5.5 % in Group 1 and 88.8 ± 10.4 and 88.8 ± 10.4 % in Group 2 (unachieved median) (р = 0.015). Cox multivariate regression analysis showed that the significant independent signs for overall survival were the pathomorphological characteristics of a tumor (risk ratio (RR) = 1.933; p = 0.010), process location (RR = 0.705; р = 0.010), and tumor grade (RR = 1.825; р = 0.010); those for relapse-free survival were the pathomorphological characteristics of a tumor (RR = 2.177; р = 0.001), regional lymph node metastases (RR = 1.543; р = 0.013), tumor localization (RR = 0.700; р = 0.014), effect of radiotherapy (RR = 1.767; р = 0.042), and tumor grade (RR = 1.754; р = 0.005).